2020
DOI: 10.1098/rspb.2020.1069
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine mediates life-history responses to food abundance in Daphnia

Abstract: Expression of adaptive reaction norms of life-history traits to spatio-temporal variation in food availability is crucial for individual fitness. Yet little is known about the neural signalling mechanisms underlying these reaction norms. Previous studies suggest a role for the dopamine system in regulating behavioural and morphological responses to food across a wide range of taxa. We tested whether this neural signalling system also regulates life-history reaction norms by exposing the zooplankton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(42 citation statements)
references
References 70 publications
4
37
1
Order By: Relevance
“…In Daphnia species, dopamine affects life-history response of the animals to the availability of food (Issa et al, 2020) and it is involved in the development of predator-induced morphological defenses (Weiss, Leese, Laforsch, & Tollrian, 2015). More specifically, studies of marine invertebrates other than sea urchins have shown that dopamine has an effect on the embryonic and early larval development in the crab Metacarcinus magister (Van Alstyne, Harvey, & Cataldo, 2014), the mussel Mytilus edulis (Beiras & Widdows, 1995), and the Pacific oyster Crassostrea gigas (Rivera Vázquez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Daphnia species, dopamine affects life-history response of the animals to the availability of food (Issa et al, 2020) and it is involved in the development of predator-induced morphological defenses (Weiss, Leese, Laforsch, & Tollrian, 2015). More specifically, studies of marine invertebrates other than sea urchins have shown that dopamine has an effect on the embryonic and early larval development in the crab Metacarcinus magister (Van Alstyne, Harvey, & Cataldo, 2014), the mussel Mytilus edulis (Beiras & Widdows, 1995), and the Pacific oyster Crassostrea gigas (Rivera Vázquez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the role of dopamine across a variety of invertebrates showed that it affects animal's behavioral response to food stimuli in cnidarians (Hanai & Kitajima, 1984), nematodes (Sawin, Ranganathan, & Horvitz, 2000), insects (Honjo & Furukubo‐Tokunaga, 2009; Wright et al, 2010), crustaceans (Van Alstyne, Nelson, Vyvyan, & Cancilla, 2006), molluscs (Kemenes, Hiripi, & Benjamin, 1990; Van Alstyne et al, 2006), and adult sea urchins (Van Alstyne et al, 2006). In Daphnia species, dopamine affects life‐history response of the animals to the availability of food (Issa et al, 2020) and it is involved in the development of predator‐induced morphological defenses (Weiss, Leese, Laforsch, & Tollrian, 2015). More specifically, studies of marine invertebrates other than sea urchins have shown that dopamine has an effect on the embryonic and early larval development in the crab Metacarcinus magister (Van Alstyne, Harvey, & Cataldo, 2014), the mussel Mytilus edulis (Beiras & Widdows, 1995), and the Pacific oyster Crassostrea gigas (Rivera Vázquez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These observations raise the question of why endogenous dopamine levels do not evolve towards higher values. Issa et al (2020) suggested this may be due to costs of high dopamine levels being paid by the offspring generation, which was not quantified in their study. Negative maternal effects on offspring size from dopamine treatments were detected.…”
Section: Introductionmentioning
confidence: 88%
“…At the physiological level, the neurotransmitter dopamine plays an important role as mediator of trait responses to food (see Barron et al, 2010 for a review on dopamine-mediated behavioural and morphological responses to food across taxa). Issa et al (2020) showed that in addition to influencing morphological and behavioural traits, dopamine can regulate life-history responses to food abundance. Specifically, in the zooplankton species Daphnia magna, exposure to dopamine caused life-history reaction norms (age at maturation, fecundity) to change in a way that resulted in higher population growth rates (calculated from maternal life history traits) when food was limited (Issa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation